The effect of income prospects, social media, and environment through motivation on student entrepreneurial interests during the COVID-19 pandemic - Netty Herawaty; Wiwik Tiswiyanti; Reni Yustien (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
This study aims to determine and analyze the effect of income prospects, social media, and environment on university studentsâ€™ entrepreneurship interest during the Covid-19 pandemic directly and indirectly through motivation. This study uses primary data by distributing questionnaires to respondents. The population of this study is active students of the Faculty of Economics and Business, Universitas Jambi, Indonesia, in the even semester of 2020/2021. The sampling size in this study is determined using Slovinâ€™s formula. The number of samples acquired is 191 students. The data is analyzed using path analysis. The results show that income prospects and social media directly affect motivation, while the environment does not directly affect motivation. The prospects of income, social media, and environment do not directly affect the interest in entrepreneurship, while motivation directly affects the interest in entrepreneurship. The motivation variable can mediate the income prospects and social media variable on the interest in entrepreneurship but cannot mediate the environmental variable in the interest in entrepreneurship.Â